Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain B.; Kadoo, Narendra Y. (Journal of Plant Biochemistry and Biotechnology, 2025)
Salinity poses a formidable challenge to agriculture, detrimentally impacting plant growth and the yield of several crops globally. Pandanus odorifer (Forssk.) Kuntze is a highly salt-stress resilient plant that grows naturally along the coastal regions of Asia, Southeast Asia, and Polynesia. It is frequently found as a frontier species along the sandy shores receiving constant salt sprays. MicroRNAs (miRNAs) play essential regulatory roles in growth, development, and combating various biotic and abiotic stresses. Thus, characterizing miRNAs and their targets is critical to understanding their roles in salt stress tolerance. Through a rigorous analysis based on homology, secondary structure and signatures of other miRNA genes, we identified 52 conserved nonredundant miRNAs from the P. odorifer transcriptome data. These miRNAs were diverse and belonged to 23 miRNA phylogenetic families. Several miRNAs, including pod-MIR156a, pod-MIR164d, and pod-MIR535d, demonstrated distinct expression patterns in response to salt stress. Their target genes exhibited opposing expression trends, corroborating the intricate miRNA-target relationship. Delving deeper into their influence, we discovered that these miRNAs mainly targeted transcription factors that are known for their pivotal roles in stress responses. We also detected four miRNA-star (miRNA*) sequences (the complementary strands of functional mature miRNAs), which supports the authenticity of the identified miRNAs. This study unveils the intricate regulatory mechanism through which miRNAs may reinforce salt stress tolerance in P. odorifer, providing a promising avenue for enhancing crop resilience to various stresses through miRNA-based strategies.
Keywords: Abiotic stress; microRNA; miRNA targets; Salinity tolerance; salt stress; Transcription factors

High levels of sinigrin trigger synthesis of fatty acids in Plutella xylostella (L.) - Barve, Pranoti R.; Barvkar, Vitthal T.; Giri, Ashok P.; Kotkar, Hemlata M. (Comparative Biochemistry and Physiology D-Genomics & Proteomics, 2025)
Diamondback moth (Lepidoptera: Plutellidae; Plutella xylostella L.) is a specialist insect of the Brassicaceae family, damaging economically important crops, such as cabbage and cauliflower. Glucosinolates, also known as `mustard oil bombs' are present in all Brassicaceae members, of which sinigrin (allyl-glucosinolate or 2-propenylglucosinolate) is a major aliphatic compound. During herbivory, glucosinolates are converted to toxic isothiocyanates that deter insect pests. P. xylostella possesses glucosinolate sulfatases that desulfate them. Such a conversion renders them unfit for degradation to toxic products. Changes in the larval performance prompted us for RNA sequencing to understand probable adaptation mechanism under sinigrin stress. Differentially expressed genes were found to be related to larval cuticle proteins. Further, gene ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses depict genes belonging to the categories, integral component of membrane, cellular processes and those involved in biosynthesis of fatty acids. Upregulation of cuticular genes viz. larval cuticle protein-17 (LCP-17), cuticular protein-19 (2CP-19) and ATP binding cassette transporter C7 (ABCC7), ABCC16 was validated by qRT-PCR. Liquid chromatography quadrupole time of flight mass spectrometry analysis of whole larvae feeding on sinigrin and their separated cuticle, depicted abundance of fatty acids. Changes in the topography of the larval cuticle were evident by scanning electron microscopy. Expression of PxABCH1 was corroborated to its role in the transport of cuticular lipids. Notably, molecular docking of PxABCH1 with cuticular fatty acids showed favorable binding interactions. To summarize, integrated transcriptomic and metabolomic analyses suggest that in response to a diet containing a high dose of sinigrin, P. xylostella re-programs metabolic pathways related to fatty acid biosynthesis that directly influence insect development.
Keywords: ABC transporter; Cuticle; Host metabolite; Metabolome; Plutella xylostella; Sinigrin; Transcriptome